Parâmetros sanguíneos de ovinos alimentados com coprodutos da bananicultura submetidos a dois métodos de secagem - Lucélia Karoline Gonçalves Barbosa (2019)
Aimed to evaluate the hemogram, protein and energy metabolites in sheep fed with banana crop residues submitted to two drying methods. A total of 30 sheep, crossbred Santa Inês x Dorper, male, non-castrated and with an average initial body weight of 26.5 kg, were distributed in a randomized block design, with five treatments: two types of residues (banana pseudostem and banana leaf hay), two drying methods (100% sun drying and 100% shade drying) and control (tifton hay). The animals received the experimental diets for 20 days and after that they were submitted to a 12-hour fasting. A collection of 4mL of blood was performed for the hemogram. We collected 6mL of venous blood to obtain plasma and serum at 0h, 3h and 6h times after feeding to evaluate the concentration of total protein, serum albumin and globulins, plasma glucose, urea, triglycerides, serum cholesterol and creatinine. The variables were analyzed in arrangement of subdivided plots and the means compared using the Dunnet test at 5% probability. Mean values of erythrocytes, hemoglobin concentration, hematocrit, mean corpuscular volume, mean corpuscular hemoglobin, concentration of mean corpuscular hemoglobin and platelets were similar (p> 0.05) between treatments, as well as mean of leukocytes, segmented neutrophils, lymphocytes, monocytes and eosinophils (p> 0.05). The mean values of total protein, serum albumin and globulins, albumin / globulin ratio and plasma glucose were similar (p> 0.05) between times and treatments. Urea and triglycerides were higher (p <0.05) in 3h after feeding and creatinine in 0h. Serum cholesterol was lower (p <0.05) in 3h after feeding. Sheep fed with pseudostem and banana leaves dehydrated by sun drying or shade drying had hemogram variables within normality and biochemical variables with few variations, indicating that these byproducts can be used in diets composition for these animals.